A FREUDIAN PSYCHOLOGICAL ISSUE OF WOMEN CHARACTERS IN DAPHNE DU MAURIER’S NOVEL REBECCA - Margawati, Prayudias (Language Circle: Journal of Language and Literature, 2010)
A literary work can be appreciated through some ways. A psychological literary approach is made within the work. A creative process model is discussed in this subject since a work of literature often be considered as writer’s creation which is sometimes related to psychological symptoms such as obsession, contemplation, sublime and some neurosis. A determination of Sigmund Freud theory mostly occurs in psychological approach applied to literature. By identifying human unconsciousness, it can be found through Du Maurier’s novel, Rebecca, that Id, Ego and Super Ego as personality theory appeared to be psychological aspects in fictional women characters. It reflects how those characters react to conflicts through the story. Keyword: psychology, unconsciousness, personality theory, women characters